Modeling the response of within-storm runoff and erosion dynamics to climate change in two Mediterranean watersheds: a multi-model, multi-scale approach to scenario design and analysis - Nunes, J. P. (2018)
Climate change in the Mediterranean is expected to lead to lower total rainfall and soil moisture, together with higher storm intensities; different vegetation types are expected to react positively or negatively to these and other changes. Climate change could therefore have positive or negative impacts on runoff and soil erosion during storms, and previous research has indicated that the impacts could be different at the field, hillslope and catchment scales. This problem was assessed for two Mediterranean watersheds by a combined application of the PROMES regional climate model, the SWAT continuous hydrological and vegetation model, and the MEFIDIS storm runoff and erosion model. PROMES results were used to estimate changes to storm rainfall intensity, while SWAT was applied with the PROMES results to estimate changes to soil moisture and saturation deficit, as well as vegetation cover. The results from both models were used to generate scenarios of changes to storm intensity (increasing), saturation deficit (increasing) and vegetation cover (increasing according to vegetation type). These scenarios were used as input for the MEFIDIS model to study the impacts of these changes on runoff and soil erosion across spatial scales for a set of storms. The simulation results indicate that (i) the increase in saturation deficit and vegetation cover is sufficient, in many cases, to decrease or counterbalance the impacts of increased storm intensity on soil erosion at all spatial scales; (ii) catchment sediment yield is noticeably more sensitive to the climate change scenarios than within-watershed soil erosion, mostly due to the impacts of changes to saturation deficit and vegetation cover on connectivity; (iii) within the watershed, impacts on soil erosion vary with landcover type, with croplands suffering the most negative impacts.